Penerapan Model Kooperatif Learning Tipe Teams Game Turnament Berbantuan Educaplay sebagai Upaya Meningkatkan Hasil Belajar Siswa - Achmad Dhohirrobbi; Luthfiya Fathi Pusposari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to improve the learning outcomes of Social Studies (IPS) for class VIII C students at MTs Negeri 1 Pasuruan through the implementation of the cooperative learning model Teams Games Tournament (TGT) assisted by Educaplay media. The background of this research is based on the low student achievement, with only 06,25% of students scoring ≥70 in the pre-action stage. This research is a Classroom Action Research (CAR) conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. Each cycle included two meetings. The results showed a gradual improvement in student learning outcomes: 46,88% in the first cycle, 59,38% in the second cycle, and 78,12% in the third cycle. This increase was due to improvements in teaching strategies, including engaging introductory activities, contextualizing materials with students’ surroundings, and group-based reward systems. The implications of this study indicate that the TGT model assisted by Educaplay successfully fosters an active, enjoyable, and competitive learning environment, which positively impacts students’ academic performance. This model can serve as an effective alternative teaching strategy for teachers seeking to enhance student engagement and achievement in the classroom.